Communication Through Hashtags in Social Movements: A Systematic Literature Review - Sylvana Virgina Agustya; Kharisma Natalia; Irwansyah Irwansyah (Riviera Publishing, 2023)
The hashtag #MeToo was launched by activist Tarana Burke in 2006 to create